Pelotherapy and magnetic field in combined treatment of bronchial asthma patients with accompanying gastrointestinal pathology - T. N. Zaripova; N. N. Simagayeva; I. I. Antipova; O. A. Anichkina; S. S. Shakhova; N. M. Yuriyeva; D. I. Kuzmenko (Бюллетень сибирской медицины, 2010)
We report a developed treatment technique with the use of physical factors for treatment of bronchial asthma patients with accompanying gastrointestinal pathology. A total of 129 patients were divided into three groups by the method of treatment: 1st (main) group (53 patients) received peaty mud applications and traveling magnetic field (TMF), 2nd group (45 patients) received TMF, and 3rd group (31 patients) received peaty mud applications. The study of the dynamics of clinical pattern, biochemical, immunological, functional, and endoscopic data has shown the efficiency of the combined application of pelotherapy and TMF, which exert the positive effect on the main and accompanying diseases and provide high immediate and long-term results of treatment.